Review Kebijakan Dividen Pada Siklus Hidup Perusahaan - Franciskus Jumintang; Jihan Zata Amani; Gilang Ahmad Fauzan; Sri Mulyantini (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
This research is in the form of a literature review which aims to determine dividend policy at each stage of the company's life cycle. The results of this literature review show that companies at the introduction or startup stage tend not to distribute dividends. At the growth stage, dividend payments tend to be low but there are companies that can make dividend payments even though the amount is not so large. Companies tend to pay dividends at the mature stage. At this stage, the company pays higher dividends compared to other stages. Meanwhile, in the decline stage, dividend payments decrease because the company is no longer able to provide large dividends.